Analysis of medium-term impact of multifunctional living mulches on soil biological fertility of an organic apple orchard - Ewa Maria Furmanczyk; Malgorzata Tartanus; Eligio Malusà (Scientific Reports)
Abstract Living mulches, particularly when designed with officinal plants, beside competing against weeds of a fruit crop, could provide other ecosystem services. The impact on soil chemical and biological features of Alchemilla vulgaris, Fragaria vesca and Mentha x piperita after four years of establishment as understorey living mulches in an organic apple orchard was evaluated. Soil nutrients level was not affected by the living mulches. The combined effect of season and living mulch affected bacterial activity, which reverberated on phyla and taxa abundance. Only few genera were unique to each living mulch species, but the abundance of 213 genera was differentially modified by the living mulches. The soil level of P and K, the metabolism of several C sources, and the bacterial activity and Shannon Index were highly correlated with the relative abundance of about a third of identified bacterial taxa. The analysis of bacterial abundance data gathered since the establishment of the trial was showing a different trend in shaping bacterial soil microbiome depending on the living mulch species.